Inventory of Plants used in Traditional Medicines in West Cikarang District - Anugrah, Devi; Nasution, Yusniar (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
This study aims to determine the types of plants used as medicine in West Cikarang District, Bekasi Regency. In modern times, knowledge about the use of medicinal plants has begun to decrease, especially for the younger generation, this is due to the limited transfer of knowledge provided (from parents to children), so that knowledge about the use of medicinal plants from this ancestral heritage needs to be preserved so as not to lost to time, and his knowledge can continue to be known Â by future generations. Therefore, it is necessary to carry out an inventory of Â medicinal plants. The research method used is descriptive qualitative. This research was conducted in March 2021. This research took place in West Cikarang District, Bekasi Regency. The results of the study found 86 species of medicinal plants consisting of 43 families. The family of medicinal plants most frequently mentioned is Zingiberaceae. The most widely used plant organs are leaves as much as 40%. The method of processing the most is by boiling as much as 39%, while the method of use that is the most mentioned is by drinking as much as 59%